Spatial and Temporal Relationships Between Roe and Red Deer in an Alpine Area - Valerio Donini; Luca Pedrotti; Francesco Ferretti; Elisa Iacona; Lucrezia Lorenzetti; Francesca Cozzi; Luca Corlatti (Ecology and Evolution)
ABSTRACT Interspecific interactions are important drivers of population dynamics and species distribution. These relationships can increase niche partitioning between sympatric species, which can differentiate space and time use or modify their feeding strategies. Roe deer Capreolus capreolus and red deer Cervus elaphus are two of the most widespread ungulate species in Europe and show spatial and dietary overlap. However, limited information is available on their interspecific relationships, especially in mountainous areas. In this study we used 5 years of camera trapping data collected in the Stelvio National Park (Central Italian Alps) to investigate spatial and temporal interactions between roe deer and red deer. Analyses were based on 2060 and 9030 roe deer and red deer detections, respectively, collected from July to September, from 2019 to 2023, using 50 camera traps randomly distributed over a 10,000‐ha study area. Spatial interactions were assessed by fitting a single‐season, single‐species occupancy model to calculate the probability of roe deer detection and occupancy as a function of relative red deer abundance and site‐specific environmental covariates. Temporal interactions were obtained by comparing the diel activity patterns of the two species. Results showed no significant effect of red deer relative abundance on the probability of presence of roe deer. Spatial analysis suggested a higher probability of roe deer presence in forested habitats, at lower elevations, and in areas with gentler slopes. Diel activity patterns of roe deer were consistent across sites with higher and lower red deer relative abundance, with moderate to high interspecific overlap, suggesting moderate temporal partitioning and no major support for temporal avoidance of the latter by the former. The high degree of overlap between the two species may be the result of area‐specific ecological conditions, such as the widespread distribution of red deer during the summer period, as well as of the adoption of strategies that favor coexistence.